2019
DOI: 10.3390/ani9040122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Factors (Weight, Body Condition, Parity, and Pregnancy Rank) on Plasma Metabolites of Dairy Ewes and Their Lambs

Abstract: Pregnancy and lactation are challenging states that affect maternal and lamb health. In Lacaune dairy sheep, we evaluated the impact of parity, pregnancy rank, and body condition on body weight and the condition of ewes and lambs in mid-pregnancy (75 ± 5 d), in late pregnancy (142 ± 4d), and postpartum (52 ± 5d pp). Maternal age was associated with initial decreases, followed by increases, in body weight and condition. After lambing, both mature and maiden ewes lost weight and body condition. Maternal indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 61 publications
6
36
0
3
Order By: Relevance
“…More recently, in cow, the CLSTN2 gene was found to play a role related to lipid metabolism, affecting carcass traits [77]. Pensante-Pacheco et al [78] reported that sheep after calving lose weight and body condition, and lambs born alone were heavier than those born in multiparous litters. Therefore, this gene can act in the metabolic pathways, mainly for the accumulation of energy reserves, allowing animals to survive food shortages that can be used by sheep in reproduction, pregnancy, and lactation; these include changes in synaptic inputs onto GnRH neurons, and the neuroendocrine system signal regulates seasonal reproduction [79].…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…More recently, in cow, the CLSTN2 gene was found to play a role related to lipid metabolism, affecting carcass traits [77]. Pensante-Pacheco et al [78] reported that sheep after calving lose weight and body condition, and lambs born alone were heavier than those born in multiparous litters. Therefore, this gene can act in the metabolic pathways, mainly for the accumulation of energy reserves, allowing animals to survive food shortages that can be used by sheep in reproduction, pregnancy, and lactation; these include changes in synaptic inputs onto GnRH neurons, and the neuroendocrine system signal regulates seasonal reproduction [79].…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…The aim of the present study was to assess the metabolic demands during pregnancy and concurrent lactation in high-producing Lacaune dairy sheep and examine the subsequent effects on maternal milk yield, offspring metabolism and body size. This work is closely related to another study in this same Special Issue [22], in which we assessed the effects of maternal body weight, condition, parity, and pregnancy rank on metabolism in ewes and their offspring.…”
Section: Introductionmentioning
confidence: 67%
“…This work was carried out concurrently with another study published in the same Special Issue of this Journal as two parts of the same project, using the same flock [22]. The study design, animals used, methods for animal handling, measurements of metabolic parameters in ewes and lambs, assessments of postnatal development, and statistical analyses were all performed as described in that work [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies varying in breed and environment confirm this general trend in body weight in young animals, but vary in magnitude ( Carrillo and Segura, 1993 ; Akpa et al, 2006 ; Stafford et al, 2007 ; Mellado, 2016 ). Some studies propose that birth type primarily influences birth weight and becomes less important as animals age ( Jucá et al, 2016; Pesántez-Pacheco et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%